Consumer Protection in Housing Buying and Buying Loans At "Griya Kademangan Beautiful" Housing Demangan Siman Ponorogo Islamic Law Perspective - Aulia, Faisal (At-Tasyri': Jurnal Hukum dan Ekonomi Syariah, 2022)
Housing is one of the basic human needs that must be met. Having your own home is everyone's dream, even a need for those who are already married. However, the soaring house prices have made it rare for people to be able to buy a house in cash, so they have to buy in installments or rent. In this study, the author uses a descriptive type of research. The data used in this research is secondary data by studying and analyzing legal materials and tertiary legal materials, namely legal materials that provide instructions and explanations for primary and secondary legal materials, namely: legal dictionaries and Indonesian language dictionaries. In this case, the researcher examines and analyzes related to legal protection in buying and selling housing on credit at Griya Kademangan Indah Demangan Siman Ponorogo housing from the perspective of Islamic law. The results of research in this writing are: In this housing use the concept of buying and selling sharia and the laws and contracts used are also different, some use Islamic law contracts and some also use contracts in law. The housing provided is also in the form of ready stock or ready-made materials, it is likely that the buyer feels satisfied in choosing the house to be inhabited, because the principle is that the buyer likes to offer what is expected by the buyer, because the conditions for a valid sale and purchase are mutual pleasure. In the sale and purchase of housing in housing "Griya Kademangan Indah" explained that in buying and selling this housing carries the concept of no usury, his can be seen in their implementation practices that they do not involve third parties, namely conventional banks and Islamic banks in their transactions, on the grounds that banks still have elements of usury. So, in payments made by consumers to housing owners, it can be directly to the housing owner, it can be content or cash and it can also be paid in installments directly to the housing owner in accordance with the agreed agreement because it does not contain an element of usury in it.